Purifying Selection Bias against Microsatellites in Gene Rich Segmental Duplications in the Rice Genome. (13th September 2012) - Sharma, P. C.; Roorkiwal, Manish; Grover, Atul
Abstract : Little data is available on microsatellite dynamics in the duplicated regions of the rice genome, even though efforts have been made in the past to align genome sequences of its two sub-species. Based on the coordinates of duplicated sequences in the indica genome as available in the public domain, we identified microsatellites in these regions. CCG and GAAAA repeats occurred most frequently. In all, 259 microsatellites could be identified in the duplicated sequences using the criteria of minimum 90% alignability spread over a minimum of 1 Kb sequence. More than 25% of the repeats in duplicated regions occurred in the genic sequences. Only 45 (17%) of these 259 microsatellites were found conserved in the duplicated paralogues. Among these repeats, 40% maintained both sequence and length conservation. The effect of mutability of nearby regions could also be clearly seen in microsatellite regions. The overall purpose of this study was to investigate, whether microsatellites follow an independent course of evolutionary dynamics subsequent to events like genome reshuffling that simply drives these elements to different locations in the genome. To the best of our knowledge, this is the first comprehensive analysis of microsatellite conservation in the duplicated regions of any genome.